Dépendance et attraction dans la poésie de Màiri MacPherson - Jean Berton (Cahiers Victoriens et Edouardiens)
Màiri MacPherson’s poetry voices the power of attraction emanating from the Isle of Skye, in the Inner Hebrides. This study means to analyse the elements producing a sense of dependence—nature, the Gaelic language, dispossession and isolation... Màiri MacPherson’s poetry combines her expression of a political rebellion with a powerful feeling of belonging. Her poems were first of all lyrics for popular songs. This implies a greater sense of sharing of feelings and opinions with her audiences constituting the whole community of Skye that were upset by the clearances and the subsequent political and economic policies.